VD_FINDINFO HC / 2021 / 120 vom 12. März 2021 - VD Tribunal cantonal (2021)
BAIL À LOYER, RÉSILIATION, RÉNOVATION D'IMMEUBLE, PROLONGATION DU BAIL À LOYER | 271 al. 1 CO, 272 CO, 272b al. 1 CO, 272c CO